SINKRONISASI LEMBAGA PENDIDIKAN HINDU DALAM MENUMBUHKEMBANGKANKARAKTER ANAK DIDIK - PERNI, NI NYOMAN (Institut Hindu Dharma Negeri Denpasar, 2017)
Environment holds sigificant roles to the child's development. The environment includes both which is deliberately organized and sets up unconsciously. It is normatively called education. There are three kinds of environment purposely created to influence the child’s development, namely: family environment, school environment and the community. Thus, three of them are called educational institution or educational unit. The educational institutions carry important roles in developing students' characters. Therefore, synchronization between the units is essential.